Socioeconomic deprivation: an important largely unrecognized risk factor in primary prevention of cardiovascular disease. (3rd October 2022) - Kimenai, D; Pirondini, L; Gregson, J; Prieto, D; Pocock, S J; Perel, P; Hamilton, T; Welsh, P; Campbell, A; Porteous, D J; Hayward, C; Sattar, N; et al.
Abstract: Background: Socioeconomic deprivation is associated with higher cardiovascular morbidity and mortality. Whether deprivation status should be incorporated in more cardiovascular risk estimation scores remains unclear. Purpose: This study evaluates how socioeconomic deprivation status affects the performance of three primary prevention cardiovascular risk scores. Methods: The Generation Scotland Scottish Family Health Study was used to evaluate the performance of three cardiovascular risk scores with (ASSIGN) and without (SCORE2, PCE) socioeconomic deprivation as a covariate in the risk prediction model. Deprivation was defined by Scottish Index of Multiple Deprivation score. The predicted 10-year risk was evaluated against the observed event rate for the cardiovascular outcome of each risk score. The comparison was made across three groups defined by the deprivation index score consisting of group 1 defined as most deprived, group 3 defined as least deprived and group 2 which consisted of individuals in the middle deprivation categories. Results: The study population consisted of 15, 506 individuals (60.0% female, median age of 51). Across the population 1, 808 (12%) individuals were assigned to group 1 (most deprived), 8, 119 (55%) to group 2, and 4, 708 (32%) to group 3 (least deprived). Risk scores based on models that did not include deprivation status significantly under predicted risk in the most deprived (6.4% observed versus 4.6% predicted for SCORE2 and 6.7% observed versus 4.7% predicted for PCE, p<0.001 for both). Both risk scores also significantly overpredicted the risk in the least deprived group (4.0% observed versus 4.7% predicted for SCORE2, p=0.007 and 4.2% observed versus 4.9% predicted for PCE, p=0.028). In contrast, no significant difference was demonstrated in the observed versus predicted risk when using the ASSIGN risk score, which included socioeconomic deprivation status in the risk model. Conclusions: Socioeconomic status is a largely unrecognized risk factor in primary prevention of cardiovascular disease. Risk scores that exclude socioeconomic deprivation as a covariate under- and overestimate the risk in the most and least deprived individuals, respectively. This study highlights the importance of incorporating socioeconomic deprivation status in risk estimation systems to ultimately reduce inequalities in health care provision for cardiovascular disease. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The British Heart Foundation.Health Data Research UK which receives its funding from HDR UK Ltd (HDR-5012) funded by the UK Medical Research Council, Engineering and Physical Sciences Research Council, Economic and Social Research Council, Department of Health and Social Care (England), Chief Scientist Office of the Scottish Government Health and Social Care Directorates, Health and Social Care Research and Development Division (Welsh Government), Public Health Agency (Northern Ireland), British Heart Foundation and the Wellcome Trust.